2019
DOI: 10.1038/s41598-019-54829-0
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy increases the incidence and diameter of abdominal aortic aneurysm in a hypoperfusion-induced abdominal aortic aneurysm animal model

Abstract: Abdominal aortic aneurysm (AAA) is a vascular disease characterized by weakening of the vascular walls. Male sex is a risk factor for AAA, and peak AAA incidence occurs in men 10 years earlier than in women. However, the growth rate of AAA is faster in women, and women have a higher mortality due to AAA rupture. The mechanisms underlying sex-related differences in AAA remain unknown. Herein, we evaluated the effects of ovariectomy (OVX) on AAA in rats. Upon evaluation of the effects of OVX and AAA induction, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Destruction of the fiber component of the aortic wall was also observed in the thoracic and abdominal aortas, suggesting a possible relationship between OVX-induced dysfunction of PVAT and destruction of vascular fibers. Decrease in 17β-estradiol levels was observed in serum of OVX female rats 3) . Decreased estrogen leads to various symptoms such as metabolic syndrome and hypertension, which cause PVAT dysfunction, and leads to vascular fiber destruction, vascular dysfunction, and attenuation of the anti-contractile effect of blood vessels 20−22) .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Destruction of the fiber component of the aortic wall was also observed in the thoracic and abdominal aortas, suggesting a possible relationship between OVX-induced dysfunction of PVAT and destruction of vascular fibers. Decrease in 17β-estradiol levels was observed in serum of OVX female rats 3) . Decreased estrogen leads to various symptoms such as metabolic syndrome and hypertension, which cause PVAT dysfunction, and leads to vascular fiber destruction, vascular dysfunction, and attenuation of the anti-contractile effect of blood vessels 20−22) .…”
Section: Discussionmentioning
confidence: 84%
“…Pathological analysis of the aortic wall of the thoracic aorta showed that OVX degraded elastic fibers and collagen fibers. Miyamoto et al reported that OVX induced degradation of vascular fibers in the abdominal aorta 3) . Johnston reported that OVX resulted in de- creased levels of smooth muscle cells (SMCs) and elastin fibers in the mouse aortic wall 10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this theory, an observational study found that women with earlier menopause were characterized by larger AAA diameters (46). The oestrogen effect has also been demonstrated in various animal AAA models (47)(48)(49)(50). Two experimental AAA studies that compared ovariectomized mice with a sham operation group showed specifically an increased expression of MMP-9 in AAA tissue in the ovariectomized group (47,48).…”
Section: Sex Steroid Hormones: Oestrogen and Testosteronementioning
confidence: 86%
“…Hypoperfusion in the aortic wall was induced as described in previous studies [ 9 , 21 , 28 ]. The infrarenal aorta was exfoliated from the perivascular adipose tissue ( Figure S1A ), and vessels branching were ligated with 5–0 silk sutures (Akiyama Seisakusyo Co., Tokyo, Japan) to block the blood supply ( Figure S1B ).…”
Section: Methodsmentioning
confidence: 99%